Prevalence, distribution and clinical significance of joints, muscles and bones in sarcoidosis: an 18F-FDG-PET/CT study. (1st September 2020) - Papiris, Spyros A.; Manali, Effrosyni D.; Papaioannou, Andriana I.; Georgakopoulos, Alexandros; Kolilekas, Lykourgos; Pianou, Nikoletta K.; Kallergi, Maria; Papaporfyriou, Anastasia; Kallieri, Maria; Apollonatou, Vasiliki; Papadaki, Georgia; Malagari, Katerina; et al.
ABSTRACT: Objectives: In Sarcoidosis joints-muscles-bones (JMBs) localizations are of the least common. 18 F-FDG-PET/CT imaging revolutionized detection of JMBs involvement by adding metabolic activity information and allowing for a comprehensive, whole-body mapping of the disease. Aim and methods: This study investigated prevalence, distribution, and clinical significance of JMBs sarcoidosis in 195 consecutive patients that underwent 18 F-FDG PET/CT examination. Results: Joint and bone involvement were encountered in 15% of patients with a mean of the maximum-standardized-uptake-value (SUVmax ) of 6.1. Most common location was the axial skeleton. Hypercalciuria was significantly more frequent in patients with osseous involvement (p = 0.003). Muscle activity (SUVmax = 2.4) was encountered in 20% of the patients, most frequently in treatment-naïve (p = 0.02). The muscles of the lower extremities were affected the most. Muscle and bone localization coexist in 50% of the cases. JMBs disease was almost asymptomatic, not related to chronicity but to pulmonary, nodal, and systemic disease. Long-term follow-up and treatment response of affected patients confirmed sarcoidosis. Conclusion: 18 F-FDG-PET/CT revealed JMBs localizations and coexistence with other organ sites supporting the concept that sarcoidosis is a systemic disease. By allowing an integrative interpretation of multi-organ involvement in the context of a pattern highly suggestive of sarcoidosis, it strongly keeps-off the diagnosis of malignancy.